The DyViS database: style-controlled recordings of 100 homogeneous speakers for forensic phonetic research - Nolan, Francis; McDougall, Kirsty; de Jong, Gea; Hudson, Toby (International Journal of Speech, Language and the Law, 2009)
The DyViS project (‘Dynamic Variability in Speech: a Forensic Phonetic Study of British English’) at the University of Cambridge has compiled a large-scale database of speech recordings which will be freely available for (non-commercial) research purposes. The database comprises recordings of 100 male speakers of Standard Southern British English, aged 18-25, undertaking four tasks involving different speaking styles: a simulated police interview, a telephone call with an ‘accomplice’, a reading passage, and a set of read sentences. This paper describes the motivation for developing the DyViS database and explains its structure, including the novel techniques developed for eliciting spontaneous yet phonetically controlled speech under simulated forensic conditions.